Educational journalism: Concept definition - G.I. Starkova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2018)
In the paper, for the first time, an attempt has been made to define the concept of educational journalism and to reveal its essence as a fundamental type of journalism in children’s and youth press. An extensive theoretical database (dictionaries and encyclopedias, dissertations, articles of Russian teachers and researchers, as well as media projects for young audiences) has been considered. The definitions of the notion “development” as the basis of educational journalism have been analyzed. It has been shown that the emergence of educational journalism and its functioning in newspapers and magazines are determined by the social request, because it is the main component of journalism for children and young people that promotes development (education, enlightenment, attitude development, formation) and socialization, personal and civil development of young people. The analysis of the definitions has shown the multidimensionality of the notion “development”, which ultimately implies a comprehensive qualitative transformation (improvement) of the child’s personality under the influence (with complicity) of an adult (parent / educator / teacher) according to age characteristics. Starting from the 19th century, Russian teachers, bibliographers, and writers uncovered the areas of development of children and young people, complementing each other, and therefore, the areas of educational journalism, which should be presented in the projects of children and young people. In general, educational journalism is the main component of journalism for the youth audience, because it contributes to the personal and civic development of the Russian youth. Examples of the implementation of various areas of educational journalism in the children’s and youth press of Udmurtia have been given.